Treatment Modification after Second-Line Failure among People Living with HIV in Asia-Pacific. Issue 7 (October 2020) - Jiamsakul, Awachana; Azwa, Iskandar; Zhang, Fujie; Yunihastuti, Evy; Ditangco, Rossana; Kumarasamy, Nagalingeswaran; Ng, Oon Tek; Chan, Yu-Jiun; Ly, Penh Sun; Choi, Jun Yong; Lee, Man-Po; Pujari, Sanjay; et al.
Background: The World Health Organization recommends continuation with the failing second-line regimen if third-line option is not available. We investigated treatment outcomes among people living with HIV in Asia who continued with failing second-line regimens compared with those who had treatment modifications after failure. Methods: Treatment modification was defined as a change of two antiretrovirals, a drug class change or treatment interruption (TI), all for >14 days. We assessed factors associated with CD4 changes and undetectable viral load (UVL <1, 000 copies/ml) at 1 year after second-line failure using linear and logistic regression, respectively. Survival time was analysed using competing risk regression. Results: Of the 328 patients who failed second-line ART in our cohorts, 208 (63%) had a subsequent treatment modification. Compared with those who continued the failing regimen, the average CD4 cell increase was higher in patients who had a modification without TI (difference =77.5, 95% CI 35.3, 119.7) while no difference was observed among those with TI (difference =-5.3, 95% CI -67.3, 56.8). Compared with those who continued the failing regimen, the odds of achieving UVL was lower in patients with TI (OR=0.18, 95% CI 0.06, 0.60) and similar among those who had a modification without TI (OR=1.97, 95% CI 0.95, 4.10), with proportions of UVL 60%, 22% and 75%, respectively. Survival time was not affected by treatment modifications. Conclusions: CD4 cell improvements were observed in those who had treatment modification without TI compared with those on the failing regimen. When no other options are available, maintaining the same failing ART combination provided better VL control than interrupting treatment.